Conformal structure of massless scalar amplitudes beyond tree level - Banerjee, Nabamita; Banerjee, Shamik; Bhatkar, Sayali Atul; Jain, Sachin (The journal of high energy physics, 2018)
A bstract We show that the one-loop on-shell four-point scattering amplitude of massless ϕ 4 scalar field theory in 4D Minkowski space time, when Mellin transformed to the Celestial sphere at infinity, transforms covariantly under the global conformal group (SL(2, ℂ)) on the sphere. The unitarity of the four-point scalar amplitudes is recast into this Mellin basis. We show that the same conformal structure also appears for the two-loop Mellin amplitude. Finally we comment on some universal structure for all loop four-point Mellin amplitudes specific to this theory.